Consumer usage intention of electronic wallets during the COVID-19 pandemic in Malaysia - Adedapo Oluwaseyi Ojo; Olawole Fawehinmi; Oluwayomi Toyin Ojo; Chris Arasanmi; Christine Nya-Ling Tan (Cogent Business & Management, 2022)
An electronic wallet (e-wallet) is the digital equivalent of a physical wallet that can support cashless and contactless payment, thereby enabling consumers' to meet the physical contact restrictions imposed to contain the spread of COVID-19. Hence, consistent with the increasing awareness of e-wallets, this study investigates consumers' intention to use e-wallets. Drawing on the motivation-ability-opportunity (MAO) framework, we investigated the factors of consumers' usage intention of e-wallets. The hypothesized model was tested using the survey data collected from 226 respondents in Malaysia. The results of partial modelling analysis of 226 respondents affirmed the significance of perceived COVID-19 risk, perceived government support, and facilitating conditions in influencing usage intention. However, effort expectancy was not a significant predictor. As hypothesized, facilitating conditions moderated the effects of effort expectancy and perceived government support on usage intention, but not that of perceived COVID-19 risk. Our findings demonstrated that motivation in terms of health risk avoidance and government incentives and opportunity in the form of facilitating conditions play significant roles in influencing the usage intention of e-wallets.
Keywords: 650; mobile payment; consumer behavior; behavioral intention; contactless transaction; E-wallet adoption; perceived risk